2016
DOI: 10.1016/j.colegn.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The WA Goldfields Aboriginal Community Antenatal Program—A community midwifery initiative

Abstract: AcknowledgementsThe authors acknowledge and thank all the women, staff and community members who have been part of this community based Aboriginal Antenatal Program. 2 Abstract AimTo investigate the acceptability and satisfaction with the Aboriginal Community Antenatal Program by staff in the program and partner agencies. DesignA Strengths, Weaknesses, Opportunities and Threats framework guided the research and data collection methods. Mixed methodology was used, accessing qualitative and quantitative informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Service coordination and effective referral links in PHC are crucial if a patient is to receive continued quality care. In our study, although health service acceptability (86%-97%) [44,65,75], and service use [63,64,68,70,89,103,104,125] (Table S7 in the Online Supplementary Document) have increased over time, the number of referrals for behavioural risks for chronic diseases was not increased [129]. Similarly, a study reported that only 38%-49% of chronic disease patients received a referral for their complex health care needs including mental health [53].…”
Section: Person / Patient-centerednessmentioning
confidence: 49%
See 2 more Smart Citations
“…Service coordination and effective referral links in PHC are crucial if a patient is to receive continued quality care. In our study, although health service acceptability (86%-97%) [44,65,75], and service use [63,64,68,70,89,103,104,125] (Table S7 in the Online Supplementary Document) have increased over time, the number of referrals for behavioural risks for chronic diseases was not increased [129]. Similarly, a study reported that only 38%-49% of chronic disease patients received a referral for their complex health care needs including mental health [53].…”
Section: Person / Patient-centerednessmentioning
confidence: 49%
“…The overall characteristics of included studies are summarized in each section of the key attributes of good PHC delivery [19]. Of 112 studies included, methodologically, 29 were qualitative studies [17,, 20 were cross-sectional [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71], 15 were mixed-method studies [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86], 10 were national / state based surveys / census [87][88][89][90][91][92][93][94][95][96], nine were retrospective / prospective cohort [97][98]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation